Pembimbingan bagi Generasi Z di GKSI Antiokhia Jakarta dalam Merespons Worship Apathy - Zega, Yanuar Ada; Hia, Yeremia; Zai, Erwin; Nome, Nehemia (Jurnal PKM Setiadharma, 2025)
The Indonesian Christian Faithful Church (GKSI) Antiochia, located in East Jakarta on Kalimalang main road, serves as the location for this Community Service implementation. Based on observations and surveys conducted, worship apathy among Generation Z appears to be quite significant, particularly in their involvement in Youth worship services. This condition is exacerbated by their high dependency on gadgets and social media, along with the minimal role of spiritual mentors in facilitating meaningful worship experiences. In response to these conditions, this Community Service program aims to fulfill the need for contextual worship guidance. The objective is for Generation Z at GKSI Antiochia to experience transformation in their worship life, understand the essence of true worship (John 4:23-24), and grow into a generation of faithful worshippers. The Community Service implementation employs participatory observation methods, personal mentoring, group discussions, and worship workshops supported by literature studies. The results demonstrate significant transformation in Generation Z's understanding and practice of worship, marked by increased involvement in church services and deepened personal relationship with God.